Technical and vocational education students’ perception of using learning videos during Covid-19 pandemic period - N., Hamzah; M. F., Ahmad; N., Zakaria; A., Ariffin; S. N. K., Rubani (2021)
The closure of Higher Education Institutions and Schools due to COVID-19 pandemic has affected the structure of Learning and Teaching (T&L) from direct method at institutions to Open and Distance Education (ODE) completely. All face-to-face T&L activities are not allowed except for certain categories of students who need to return to campus in stages to participante in T&L activities in full compliance of the Standard Operating Procedures (SOP) set by prioritizing safety measures and social distancing. This study used a quantitative approach by using online questionnaire as instrument (google form). A total of 73 Technical and Vocational Education (TVE) students from various backgrounds of respondents participated in the study. The findings of the study showed that there was a strong correlation between the aspects of interest and gender of TVE students in using learning videos during the COVID-19 pandemic period (r = .701). Therefore, all parties must prepare to face the new norm, namely the ODL method as a whole during the COVID-19 pandemic period to continue the T&L process for students.